The definition of anti-Semitism - Marcus, Kenneth L. (Oxford University Press, 2015)
"The definition of anti-Semitism explores the ways in which anti-Semitism has historically been defined, demonstrates the weaknesses in prior efforts, and develops a new definition of anti-Semitism"..